THE SETTLEMENT OF MEDICAL ETHICS CODE INFRACTIONS AT RSUD Dr. SOEWANDHIE SURABAYA - Grascillia, Anggie; Sushanty, Vera Rimbawani (jfpublisher, 2023)
Indonesian Honorary Council of Medical Ethics (MKEK) is one of the autonomous institutions of the Indonesian Medical Association that is formed especially at the national, regional, and branch levels to perform professional ombudsman duties, foster professional ethics and/or other institutional and ad hoc duties at their respective levels. The Medical Ethic Code in Indonesia has been regulated in the Decree of the Health Minister Number 434/2002 by the IDI management which has revised and established changes to the results of the national working meeting on medical ethics in 2001. The type of research used is empirical jurisdiction which in its research uses a problem approach regarding medical ethics code infractions at RSUD Dr. Soewandhie Surabaya. The data sources used are (1) primary data sources, such as observation and interviews; and (2) secondary data sources, such as data sources that support the primary data sources (law books, scientific papers, articles, and so on). This research technique used purposive sampling technique. The research results indicated that legal protection against violation of the medical ethic code can be resolved in two ways, such as the criminal process (litigation) and the civil process (non-litigation) in which the initial settlement process is assisted by the Ethics Honorary Council, then further handled by the Medical Ethics Committee through mediation related to the provision of sanctions.